2023
DOI: 10.1371/journal.pone.0289264
|View full text |Cite
|
Sign up to set email alerts
|

Is the profitability of Islamic and conventional banks driven by the same factors?—A study of banking in the Middle East

Iwona Sobol,
Łukasz Dopierała,
Przemysław Wysiński

Abstract: The purpose of this paper is to contribute to the existing literature by investigating the determinants of the profitability of Islamic and conventional banks in the Middle East region and revealing the most important factors for these two types of banks. Few papers have studied the performance of Islamic banks and compared their performance with conventional banks. The results from these limited research papers are also various, mainly because the sample sizes are small, or they have analysed data only from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
1
3
0
3
Order By: Relevance
“…Strategi pendanaan yang diterapkan oleh bank mempengaruhi profitabilitas secara keseluruhan, dengan tingkat aset yang didanai oleh deposito yang lebih rendah akan meningkatkan profitabilitas (O'Connell, 2023). Dengan mengembangkan penelitian terbaru yang sudah ada terkait faktor-faktor penentu profitabilitas perbankan, antara lain CASA dalam melihat posisi likuiditas perbankan (Mehzabin et al, 2023;Sobol et al, 2023;Shen et al, 2023;O'Connell, 2023;Pham & Nguyen, 2023;Ayalew, 2021;Mohanty, 2021;Farhadi & Fooladi, 2021;Pak, 2020;Ghosh & Sanyal, 2019).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Strategi pendanaan yang diterapkan oleh bank mempengaruhi profitabilitas secara keseluruhan, dengan tingkat aset yang didanai oleh deposito yang lebih rendah akan meningkatkan profitabilitas (O'Connell, 2023). Dengan mengembangkan penelitian terbaru yang sudah ada terkait faktor-faktor penentu profitabilitas perbankan, antara lain CASA dalam melihat posisi likuiditas perbankan (Mehzabin et al, 2023;Sobol et al, 2023;Shen et al, 2023;O'Connell, 2023;Pham & Nguyen, 2023;Ayalew, 2021;Mohanty, 2021;Farhadi & Fooladi, 2021;Pak, 2020;Ghosh & Sanyal, 2019).…”
Section: Pendahuluanunclassified
“…BOPO untuk melihat seberapa efisien dalam operasional dalam menghasilkan profitabilitas (Sobol et al, 2023;Mehzabin et al, 2023;Pham & Nguyen, 2023;Ghosh & Sanyal, 2019), dan LDR untuk melihat kapasitas pendapatan dari penyaluran kredit (Ayalew, 2021;Al-Matari, 2023;Khalifaturofi'ah, 2023;Farhadi & Fooladi, 2021) serta menambah literatur perbankan di Indonesia yang sudah ada terkait faktor penentu profitablitas perbankan (Khalifaturofi'ah, 2023;Anindyajati & Hanggraeni, 2022;Khabibah et al, 2020;Andhikatama, Muda, & Daulay, 2016). Penelitian ini akan berfokus kepada financial perfomance di dalam heterogenitas perusahaan berdasarkan KBMI terbaru dan periode tahun (PRE-Covid-19 dan POST-Covid-19) untuk melihat profitabilitas perbankan di Indonesia dengan menguji beberapa rasio keuangan, posisi likuiditas perbankan (CASA), kapasitas operasional (BOPO), dan kapasitas pendapatan dari penyaluran kredit (LDR) dalam menghasilkan profit.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…While Ghouse et. al., (2022) and Sobol et. al., (2023) found that Islamic banks exhibited superior performance compared to conventional banks during pandemic Covid-19 in Organization of Islamic Cooperation (OIC) countries.…”
Section: Introductionmentioning
confidence: 96%
“…Emerged as an alternative banking and finance model, this type of banking operates according to the principles of shariah, which prohibits interest (riba), uncertainty (gharar), gambling (maysir), and other unethical practices (Siddique et al, 2023). Thus, Islamic banks (therefore IB) should contribute richly to the achievement of the major socio-economic goals of Islam such as economic prosperity with full employment and an optimum rate of economic growth, socio-economic justice, and equitable distribution of wealth and monetary stability (Sobol et al, 2023). In order to ensure this ethicality, they need to conduct operations in accordance with the principles of shariaa.…”
Section: Introductionmentioning
confidence: 99%